Problematika Dakwaan Tindak Pidana Pembunuhan Berencana Dengan Pembunuhan Biasa - Hanif Hawari Mohamad; Muhamad Sadam Alamsyah; Herli Antoni (Deposisi: Jurnal Publikasi Ilmu Hukum, 2023)
This research aims to examine the problems that occur in the crime of murder and premeditated murder in the charges that will be filed against the perpetrators of these crimes. At the beginning, the background will be about how a criminal law in Indonesia develops and in carrying out its function as a legal rule that contains provisions, prohibitions, and criminal threats for those who commit a criminal case. This research will emphasize the problems that occur with the obstacles experienced by law enforcement in identifying a legal event that occurs in the case of murder with premeditated murder in finding an element of fulfillment, especially against the elements of the offense of premeditated murder. Then after that, the research will continue on legal reconstruction and legal discovery at the court hearing which aims to facilitate the disclosure of a legal event that occurs in order to find the material truth so that the judge can determine the sentence for the perpetrator.